2021
DOI: 10.3389/fonc.2020.611571
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Lesion Histogram Analysis of the Apparent Diffusion Coefficient as a Quantitative Imaging Biomarker for Assessing the Level of Tumor-Infiltrating Lymphocytes: Value in Molecular Subtypes of Breast Cancer

Abstract: PurposeTo assess whether apparent diffusion coefficient (ADC) metrics can be used to assess tumor-infiltrating lymphocyte (TIL) levels in breast cancer, particularly in the molecular subtypes of breast cancer.MethodsIn total, 114 patients with breast cancer met the inclusion criteria (mean age: 52 years; range: 29–85 years) and underwent multi-parametric breast magnetic resonance imaging (MRI). The patients were imaged by diffusion-weighted (DW)-MRI (1.5 T) using a single-shot spin-echo echo-planar imaging seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Various ADC histogram parameters were calculated: 10th percentile, mean, 50th percentile (median), 90th percentile, skewness (a measure of asymmetry of the histogram about its mean), kurtosis (a measure of the peakedness of the histogram), and entropy (measure of the variation in the histogram distribution). We followed the methods of Tang et al [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various ADC histogram parameters were calculated: 10th percentile, mean, 50th percentile (median), 90th percentile, skewness (a measure of asymmetry of the histogram about its mean), kurtosis (a measure of the peakedness of the histogram), and entropy (measure of the variation in the histogram distribution). We followed the methods of Tang et al [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…The ADC measurements in the previous study were mostly based on traditional 2D regions of interest (ROIs) manually drawn from a single representative slice of the breast lesion, which might limit these ADC measurements in their ability to reflect whole tumour characteristics [4,[8][9][10][11]. Assessments with whole volume histogram analyses of the ADC might provide more reliable results to reflect the biological characteristics of the heterogeneous breast lesions [3,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…While image-based assessments will likely neither supplant nor substitute for the current gold standard of tissue-based assessment, we posit that our radiographic methodology would be helpful in promoting long-term evaluation and in vivo surveillance of the TME. In fact, some researchers have surveyed the relationship between radiographic features and tumor-invading lymphocytes (10)(11)(12), and the ability of radiomic features to predict prognosis (12). Fertéet al correlated both on-tumor and peri-tumor radiomic features with CD8 expression at the central tumor area and suggested that imaging features might help assess the CD8 cell population and also forecast the clinical response for those patients receiving antibody therapy (11).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of radiologic images by quantified radiomics methods can reveal associations between particular images with molecular phenotypes (9). And some investigators have already begun exploring the relationships between imaging features and tumor-infiltrating lymphocytes (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…For the breast, ADC histogram analysis also revealed ADC kurtosis to be higher in breast cancer of triple-negative than breast cancer of estrogen receptor-positive subtype [ 34 ]. Whole-lesion histogram analysis of the ADC could be used as a qualitative imaging biomarker for the tumor-infiltrating lymphocyte levels in breast cancer [ 35 ]. Maximum whole tumor ADC values may be used to differentiate luminal cancers from other molecular subtypes of breast tumors [ 36 ].…”
Section: Discussionmentioning
confidence: 99%